Mobile and Portable Specimen Collection Unit - Rinen, Richard Martin; Jose, John Ernest; Espina, Cristopher Stonewall (Sanyata, 2025)
Designed to combat the challenges of COVID-19 testing, the specimen collection unit (SCU) offers safe, efficient, and accessible swab collection, bringing testing directly to communities.